Effects of viscous dissipation and wall conduction on steady mixed convection couette flow of heat generating/absorbing fluid - Ajibade, Abiodun O.; Umar, Ayuba Muhammad (Zielona Góra: Uniwersytet Zielonogórski)
This article theoretically investigate mixed convection flow of heat generating/absorbing fluid in the presence of viscous dissipation and wall conduction effects. The flow is considered to be steady in a vertical channel with some boundary thickness. One of the plates is heated while the other is kept at ambient temperature.
Keywords: mixed convection; viscous dissipation; vertical channel; boundary thickness; mass constant flux